The Urgent Need in the Capitalization of Social and Psychological Components of the Scientific and Engineering Potential Capacity - Popovych, O.S. (Science and Innovation, 2024)
The problems of fall in the national science social capital have been analyzed, with attention focused on the fact that the level of science support by the state and the industry depends not only on the economic situation, but mostly on its authority in the society and the public confidence, i.e. on the external component of science social capital. The necessity of consolidating efforts of the scientific community towards popularizing the achievements of national science and the formation of large-scale program of activities to increase the authority of science, in general, and the National Academy of Sciences of Ukraine, in particular, has been substantiated.